SISTEM INFORMASI PERSEDIAAN BARANG DI TOKO ADI SURYA MENGGUNAKAN METODE FIFO BERBASIS WEB - Imam Tri Suryadin (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2022)
Inventory information system with the FIFO method is an information system to find out the stock of goods in a company. FIFO itself is a method of spending by removing the first goods that enter in order to prevent a decrease in quality. In this study, the data collection method used a literature study. This information system is prepared by designing a structured model system, its implementation using PHP as the programming language and MySql as the database. From the research conducted, an inventory information system software was produced using the WEB-based FIFO method. With this system the user can find out the system for recording incoming goods, outgoing goods and a more structured stock of goods. Keywords: FIFO, Inventory, MySQL, WEB.